LITERATURE REVIEW OF FINANCE INFORMATION SYSTEM: ADMINISTRATION, FINANCIAL ACCOUNTABILITY AND ORGANIZATIONAL COMMITMENT - Oktavia, Yohana (Dinasti Publisher, 2022)
Previous research is very important in a scientific research or article. The relevant riset serves to reinforce the theory and influence between variables. This article reviews the factors that affect the Finance Information System, namely: Administration, Financial Accountability and Organizational Commitment. The main purpose of writing this article is to build a hypothesis of influence between variables for use in future research. The results of this literature review article are: 1) The administration affects the System Finance Information; 2) Financial Accountability affects the Finance Information System; and 3) The Organization's Commitment affects the Finance Information System.